Distribution patterns of the invasive species Robinia pseudacacia in NE Slovenia - Ribeiro, Daniela; Čarni, Andraž; Somodi, Imelda (Anali PAZU, 2022)
Robinia pseudacacia L. was introduced into Europe at the beginning of the 17th century and is now considered to be an invasive species also in Slovenia. Our study area was located in northeastern Slovenia, within the Prekmurje region. The aim of our study was to find explanations for the current occurrence pattern of the species in that location. Areas dominated by R. pseudacacia have been mapped in a scale of 1:5.000 in the lowland area of Prekmuje, across a sample plot of 4 by 3km in 2009. We analyzed potential factors that can influence the distribution of the species within the region: distance to the road network, distance to water bodies, elevation, land use, soil type and soil quality. We performed a spatial randomized sampling technique stratified for prevalence on the resulting maps in order to collect observations on the relationship between R. pseudacacia presence and the potential influenting factors.